Partial breast irradiation after sentinel lymph node biopsy omission: Is it a valid alternative to whole breast Irradiation? Analysis of the dose to the sentinel lymph node region during whole breast irradiation vs. partial breast irradiation - Sophie T. Behzadi; Rebecca Moser; Mathias Düsberg; Maximilian Aigner; Jana Nano; Sophia Kiesl; Jacqueline Lammert; Evelyn Klein; Georg P. Schmidt; Marion Kiechle; Thomas Huber; Stefanie Corradini; et al. (Breast)
Background: Sentinel lymph node biopsy (SLNB) can be safely omitted in selected early-stage, clinically node-negative breast cancer (BC) patients. While these patients are also candidates for partial breast irradiation (PBI), the dosimetric effects of PBI on the sentinel lymph node region (SLNs) and axillary levels remain unclear. Methods: In this study, SLNs were identified and contoured in 100 BC patients using pre- and postoperative imaging. Axillary levels were contoured following ESTRO guidelines. Dose distribution to the SLN (n = 9000 data points) and axillary levels (n = 270 data points) were analyzed for whole breast irradiation (WBI) and PBI across different techniques (3D-conformal radiation therapy [3D-CRT] vs. volumetric modulated arc therapy [VMAT]), deep inspiration breath-hold [DIBH] vs. free breathing [FB]), and anatomical variations (breast size, tumor site, and upper breast border). Results: WBI provided full therapeutic dose coverage (>95 % of the prescribed dose) to 65 % of SLNs, compared to only 10 % (3D-CRT) and 3 % (VMAT) with PBI. DIBH significantly reduced dose distribution to SLN and axillary levels compared to FB. Lower incidental dose coverage was also observed in patients with medial/central tumors, smaller breasts, and lower upper breast borders. Conclusion: These results demonstrate that PBI delivers substantially lower incidental dose to the SLN than WBI. Since patients in the INSEMA and SOUND trials were predominantly treated with WBI, combining SLNB omission with PBI should not be considered a standard approach and warrants further investigation.